1991
DOI: 10.2166/wst.1991.0513
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fixation in the Sludge Treatment System of a Biological Phosphorus Removal Process

Abstract: One of the major problems connected with the biological phosphorus removal process is that the phosphorus absorbed by the activated sludge may be released if the sludge is handled incorrectly, and this makes it difficult to treated sewage efficiently. Therefore, phosphorus in the return water from the sludge treatment process must be carefully controlled and reduced. Lime and ferric chloride were added to fix phosphorus in the digestion tank. Phosphorus fixation improved with the addition of lime. The digestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…The precipitation of struvite was reported to be an effective method for the recovery of nitrogen and phosphorus in several anaerobically digested wastewaters such as swine and calf wastewater, coke manufacturing, landfill leachate, leather tanning, dairy manure, etc. (Fujimoto et al, 1991;Battistoni et al, 1997Battistoni et al, , 2000Li et al, 1999;Schuiling and Andrade, 1999;Munch and Barr, 2001;Nelson et al, 2003;Uludag-Demirer et al, 2005). However, there is only one study reported in which struvite precipitation was carried out during the AD of a food waste in a digester (Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation of struvite was reported to be an effective method for the recovery of nitrogen and phosphorus in several anaerobically digested wastewaters such as swine and calf wastewater, coke manufacturing, landfill leachate, leather tanning, dairy manure, etc. (Fujimoto et al, 1991;Battistoni et al, 1997Battistoni et al, , 2000Li et al, 1999;Schuiling and Andrade, 1999;Munch and Barr, 2001;Nelson et al, 2003;Uludag-Demirer et al, 2005). However, there is only one study reported in which struvite precipitation was carried out during the AD of a food waste in a digester (Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As for the required alkaline condition of an elevated pH in the MAP system, it can be achieved by alkaline addition or pre-aeration (Battistoni et al, 1998). A study performed by Fujimoto et al (1991) has demonstrated that addition of NaOH is more effective than addition of lime or Mg(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Chemically bound P in soil could become available to plant under certain biogeochemical conditions, serving as a natural reservoir of "slow-release" P 13 . However, the slow release characteristics of soil bound P are affected by many uncontrollable factors, such as temperature, humidity, organic acid secreted by crop roots, soil pH, and soil mineral composition [14][15][16][17] . Thus, P released under these conditions cannot fulfill the crop P demand, especially during the critical growth period.…”
mentioning
confidence: 99%